KUALITAS PELAYANAN PADA EVENT BAKAR TONGKANG DI BAGAN SIAPIAPI KABUPATEN ROKAN HILIR RIAU - Rarasati, Gembira; Arief, Andi M Rifiyan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Bagan Siapi-Api is Chart has a variety of interesting cultures to visit, one of the festivals that has always been a tourist destination that is Bakar Tongkang Event. Therefore, the authors want to know the quality of services provided by the Department of Tourism, Youth and Sports Rokan Hilir Riau to tourists who visited the Bakar Tongkang Event.This study aims to determine the responses of respondents to services provided by officers during the event took place. This research uses quantitative descriptive method to examine and raise the problem by distributing questionnaires to respondents who visited the event or respondents who previously visited the event. The sample used in this study was 100 respondents, sampling technique used Nonprobability Sampling. Data collection techniques used Observation, Questionnaire, interview and documentation method. Technique Measurement Data using Likert Scale.From result of research consist of 5 sub variable that is Tangibles with good result, Realibility with good result, Responsiveness with good result, Assurance with good result and Emphaty with good result. By looking at the results of the recapitulation of the 5 sub-variables it is known that the Quality of Service at the Bakar Tongkang Event has been said Good.Keywords: Quality of Service, Event, Tangibles, Reliability, Responsiveness, Assurance and Emphaty